Always Consider the Possibility of Opioid Induced Respiratory Depression in Patients Presenting with Hypercapnic Respiratory Failure Who Fail to Improve as Expected with Appropriate Therapy. (29th March 2015) - Steynor, Martin; MacDuff, Andrew
Abstract : Hypercapnic respiratory failure is a frequently encountered medical emergency. Two common causes are acute exacerbations of chronic obstructive pulmonary disease (COPD) and as a side effect of opioids. The two causes may coexist leading to diagnostic confusion and consequent delay in optimal management. We report a case of what was initially thought to be an exacerbation of COPD. The patient failed to improve with treatment as expected which led to the empirical administration of naloxone resulting in a dramatic reversal of her respiratory failure. The patient was subsequently discovered to be taking regular dihydrocodeine for chronic back pain.